2018
DOI: 10.1111/tri.13276
|View full text |Cite
|
Sign up to set email alerts
|

ANRILas a genetic marker for cardiovascular events in renal transplant patients - an observational follow-up cohort study

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality in kidney transplant recipients. Several single-nucleotide polymorphisms (SNPs) in the ANRIL gene pathway have been associated with cardiovascular events (CE). The main objective was to ascertain whether ANRIL (rs10757278) and CARD8 (rs2043211) SNPs could mediate susceptibility to CE. This was an observational follow-up cohort study of renal transplant recipients at Bellvitge University Hospital (Barcelona) from 2000 to 2014. A total of 505… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Although the expression and functions of lncRNAs in stroke and neuroprotection remain not to be clarified [11], increasing evidence have prove that lncRNAs are closely involved in IS, such as maternally expressed gene 3 (MEG3), H19, CaMK2D-associated transcript 1 (C2dat1), Fos downstream transcript (FosDT), small nucleolar RNA host gene 14 (SNHG14), and taurine-upregulated gene 1 (TUG1) which have been found to affect cell apoptosis, inflammation, cell death, and angiogenesis in IS [12]. For example, previous study reported that lncRNA antisense non-coding RNA in the INK4 locus (ANRIL) has been related with a higher risk of developing cardiovascular events and ANRIL was demonstrated to be associated with IS [13]. Meanwhile, ANRIL was reported to play a role in inflammatory responses and atherosclerosis [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the expression and functions of lncRNAs in stroke and neuroprotection remain not to be clarified [11], increasing evidence have prove that lncRNAs are closely involved in IS, such as maternally expressed gene 3 (MEG3), H19, CaMK2D-associated transcript 1 (C2dat1), Fos downstream transcript (FosDT), small nucleolar RNA host gene 14 (SNHG14), and taurine-upregulated gene 1 (TUG1) which have been found to affect cell apoptosis, inflammation, cell death, and angiogenesis in IS [12]. For example, previous study reported that lncRNA antisense non-coding RNA in the INK4 locus (ANRIL) has been related with a higher risk of developing cardiovascular events and ANRIL was demonstrated to be associated with IS [13]. Meanwhile, ANRIL was reported to play a role in inflammatory responses and atherosclerosis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous study reported that lncRNA antisense non-coding RNA in the INK4 locus (ANRIL) has been related with a higher risk of developing cardiovascular events and ANRIL was demonstrated to be associated with IS [13]. Meanwhile, ANRIL was reported to play a role in inflammatory responses and atherosclerosis [13,14]. Moreover, one former study demonstrated that lncRNA ANRIL altered the expressions of vascular endothelial growth factor (VEGF) and apromoted ngiogenesis in rats [15], which provided potential effects of ANRIL in IS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the involvement of antisense RNAs in cardiac diseases via diabetes, antisense transcription/transcripts are also directly associated with cardiovascular diseases. Recent studies have implicated antisense RNAs as new diagnostic markers with therapeutic potentials for cardiovascular diseases [210,211,212,220,221,222,223,224,225,226,227,228,229,230,231,232,233,234,235,236,237,238,239]. For example, an antisense transcript H19, discussed above, is associated with cardiovascular diseases such as CAD.…”
Section: Antisense Transcription In Diabetes Cardiovascular and Omentioning
confidence: 99%
“…been investigated with large-scale GWAS approaches, although a handful of recent candidate gene studies have been published. [19][20][21][22] Given that etiologic factors explaining CV disease in RTRs might differ somewhat from those in the general population, one cannot automatically assume that the composite GRS investigated by Mega et al is valid for the transplant population. We therefore aimed to evaluate the predictive value of the risk score in RTRs by genotyping patients from the Assessment of Lescol in Renal Transplantation (ALERT) trial, 23,24 a study of mostly Caucasian, stable, and well-characterized RTRs followed for 7-8 years for validated clinical endpoints, including major cardiovascular events (MACEs).…”
Section: Genetic Variants In Relation To CV Outcome In Rtrs Have Not Yetmentioning
confidence: 99%
“…[19][20][21][22] Given that etiologic factors explaining CV disease in RTRs might differ somewhat from those in the general population, one cannot automatically assume that the composite GRS investigated by Mega et al is valid for the transplant population. [19][20][21][22] Given that etiologic factors explaining CV disease in RTRs might differ somewhat from those in the general population, one cannot automatically assume that the composite GRS investigated by Mega et al is valid for the transplant population.…”
Section: Introductionmentioning
confidence: 99%